2021
DOI: 10.1136/bmjophth-2021-000774
|View full text |Cite
|
Sign up to set email alerts
|

Role of amyloid β-peptide in the pathogenesis of age-related macular degeneration

Abstract: Age-related macular degeneration (AMD) is the most common eye disease in elderly patients, which could lead to irreversible vision loss and blindness. Increasing evidence indicates that amyloid β-peptide (Aβ) might be associated with the pathogenesis of AMD. In this review, we would like to summarise the current findings in this field. The literature search was done from 1995 to Feb, 2021 with following keywords, ‘Amyloid β-peptide and age-related macular degeneration’, ‘Inflammation and age-related macular de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 65 publications
1
7
2
Order By: Relevance
“…Second, it remains to be seen whether the retina of humans expresses AβOs in various degenerative pathologies. This possibility is consistent with reports linking Aβ to neurodegenerative disorders of the retina, not only AD [124] but also macular degeneration and glaucoma [124][125][126][127]. In addition, experimental type diabetes in rabbits, another species which has the human Aβ42 sequence, has been shown to induce retina AβOs [128].…”
Section: Important Questions For the Futuresupporting
confidence: 91%
“…Second, it remains to be seen whether the retina of humans expresses AβOs in various degenerative pathologies. This possibility is consistent with reports linking Aβ to neurodegenerative disorders of the retina, not only AD [124] but also macular degeneration and glaucoma [124][125][126][127]. In addition, experimental type diabetes in rabbits, another species which has the human Aβ42 sequence, has been shown to induce retina AβOs [128].…”
Section: Important Questions For the Futuresupporting
confidence: 91%
“…Of note, AD has been associated with AMD. In particular, it has been demonstrated that Aβ oligomers are involved in AMD pathogenesis [4,29], with the extracellular deposits of these species leading to the formation of drusen [5]. Additionally, AD and AMD share common pathophysiological features, including oxidative stress and neuroinflammation [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, vision-related alterations are common in AD, and visual defects are due to either degeneration of the visual cortex or to retinal degeneration associated with glaucoma and AMD. Several pieces of evidence indicate that the oligomeric form of amyloid-β (Aβ) peptide, one of the main actors in AD-related neurodegeneration, might be associated with AMD pathogenesis [4]. In particular, Aβ aggregates constitute the drusen deposits, resulting in chronic low-level inflammation and impairment of the retinal barrier [5].…”
Section: Introductionmentioning
confidence: 99%
“…VEGF expression in the RPE is significantly increased by the synergistic action of TGFβ2 and TNFα, as well as that of TGFβ2 and thrombin [ 125 , 216 , 217 , 218 ]. Increased ROS production by mitochondria also contributes to the accumulation of the amyloid β protein and leads to the excessive secretion of VEGF [ 219 ].…”
Section: Key Components In the Mechanisms Of Oxidative Stress Realiza...mentioning
confidence: 99%
“…Simultaneously, nitric oxide inactivates the PP2A catalytic subunit, which leads to increased phosphorylation of vimentin, which is a substrate for this phosphatase [ 248 ]. OS-mediated accumulation of Aβ induces inflammatory activity, oxidative phosphorylation dysregulation, angiogenesis, and cytoskeleton destabilization, causing a large amount of damage in the subretinal region, which is associated with the pathogenesis of AMD [ 219 , 249 ]. Aβ dislocates occludin and decreases the levels of occludin and zonula occludens-1 mRNA expression in RPE cells.…”
Section: Key Components In the Mechanisms Of Oxidative Stress Realiza...mentioning
confidence: 99%